TRANSRELATION DES FORMES DE MISES EN SCENE DISCURSIVES AU CAMEROUN : QUAND LE POLITIQUE SE SACRALISE - Clébert Agenor NJIMENI NJIOTANG; Michel Narcisse NTEDONDJEU (Anadiss, 2014)
This work of discourse analysis ventures into the rhetorical arrangement of meeting speeches of two Cameroonian political leaders by juxtaposing them to evangelization speeches so as to show how transrelation proceeds in their forms of discursive staging. By equally paying attention to some extralinguistic parameters that more bring closer the political meeting to religious celebration, this work finally reveals that the glorification of the politician does not only pass through a marked religiosity of different levels of discursive layout, but also through a liturgical character of this type of political encounter.